(untitled) (Journal of Economic Research & Business Administration, 2018)
There is a substantial literature on the relationship between gender and access to finance.The purpose of this research paper is to investigate the impact of gender on the usage of different funding sources in a sample of Kazakh small- to medium-sized enterprises. Most studies have been concerned with access to debt finance however this was not done in Kazakhstan in tge scope of used literature.The database includes variables on terms of credit for the firms’ unofficial loans and detailed information on the firms’ banking relationships. The total number of firm-year observations in the database is 56. The analysis is based on multivariate tests. The funding patterns of women-owned enterprises and men-owned enterprises in the data are different. The results also contradict prior studies, which indicate that MOE have easier access to bank lending. The results suggest that there are no gender-related differences in the use of bank debt. But this research accepts the theory that MOE have nore access to unofficial finance. The results of study both confirm and contradict the results of prior research and the paper suggests that this is due to the context-specific features of the Kazakh labour market and the gender system as well as the bank-centered financial markets. Practical implications – concerning the issues of gender and finance, policy makers and financial experts in any country should not uncritically rely on the research results arrived at in other countries.